Implications of the Euro - Baimbridge, Mark; Burkitt, Brian; Whyman, Philip (Taylor & Francis, 2006)
To date, critical analysis of the EMU project has largely been advanced from the centre-right spectrum of British politics. Comparable questions from the centre-left have failed to find a coherent voice. Although, the European fault-line cannot be characterized as a neat Left-Right issue there are noticeable divisions in opinion across British business, the trade union movement and within the Labour Party. Offering a unique insight into this key debate from the 'centre-left', eurosceptic view point, this book provides a rigorous analysis of all the salient economic and political issues of concern, such as: * the economics of a single currency * employment and social implications * sovereignty * political determination. The arguments presented in this volume highlight the emergence of a coherent alternative to deepening economic integration as a platform to build a just and equitable society. Contributions are drawn from leading academics, trade union leaders and prominent politicians, both from the Labour Party and the wider progressive Left in British politics. This informative and thought provoking book will be indispensable reading for students and practitioners in economics, politics and international relations, as well as those interested in this highly contentious topic.